Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1038/s41368-023-00253-0
|View full text |Cite
|
Sign up to set email alerts
|

MLL1 inhibits the neurogenic potential of SCAPs by interacting with WDR5 and repressing HES1

Chen Zhang,
Weilong Ye,
Mengyao Zhao
et al.

Abstract: Mesenchymal stem cell (MSC)-based therapy has emerged as a promising treatment for spinal cord injury (SCI), but improving the neurogenic potential of MSCs remains a challenge. Mixed lineage leukemia 1 (MLL1), an H3K4me3 methyltransferases, plays a critical role in regulating lineage-specific gene expression and influences neurogenesis. In this study, we investigated the role and mechanism of MLL1 in the neurogenesis of stem cells from apical papilla (SCAPs). We examined the expression of neural markers, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
0
0
Order By: Relevance
“…Following in vivo SCI engraftment, the literature has consistently shown that DSCs readily differentiate into GFAP, S-100 and APC/MBP-expressing astrocytes [97,102], Schwann cells [97], and oligodendrocytes [87], and importantly, induce neural progenitor cell proliferation [94,115,118]. While DSCs have also been demonstrated to differentiate into neuronal-like cells in vitro [88] and in vivo after SCI through neuronal marker staining [101,102,116], functional analysis of differentiated neurons is less frequently conducted to substantiate these findings.…”
Section: Tissue Preservation and Regenerationmentioning
confidence: 99%
“…Following in vivo SCI engraftment, the literature has consistently shown that DSCs readily differentiate into GFAP, S-100 and APC/MBP-expressing astrocytes [97,102], Schwann cells [97], and oligodendrocytes [87], and importantly, induce neural progenitor cell proliferation [94,115,118]. While DSCs have also been demonstrated to differentiate into neuronal-like cells in vitro [88] and in vivo after SCI through neuronal marker staining [101,102,116], functional analysis of differentiated neurons is less frequently conducted to substantiate these findings.…”
Section: Tissue Preservation and Regenerationmentioning
confidence: 99%